Kebudayaan Nasional dan Kesadaran Nasional: Analisis Pemikiran Sanusi Pane - Reski Putra Utama (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2020)
Sanusi Pane is phenomenal literalist. Sanusi Pane has his own opinion about national awareness and national culture which conclude in every his own literally work, Sanusi Pane has tried to build national awareness by his own way. Sanusi Pane tried to love the father land by reminding the history at past which is implicit in one of his poem, entitled “Majapahit”. One of his essay which entitled “Mengembalikan Kebudajaan Kita”, Sanusi argued that Indonesia culture which priority in spiritual life, sense, cooperate, and help each other.